The impact of remittances on economic activity in the region of Central and Southeastern Europe - Mite Miteski (Economy, Business and Development: An International Journal (EB&D), 2024)
This research aims to investigate the impact of remittances on economic growth in Central and Southeastern Europe by employing panel unobserved effects methodology across twelve selected countries within the region (CSEE-12). Our motivation arises from the fact that these countries are among the highest recipients of private remittances in Europe, suggesting that such financial inflows could potentially have a significant influence on fostering their economic growth. The empirical findings provide evidence that remittances indeed exert a positive and significant direct effect on economic growth in the analyzed group of countries, along with some of the other standard growth factors, such as physical and human capital.
Keywords: F21; F43; C23; O47; 330; Central and Southeastern Europe; economic growth; panel estimation; Remittances